Balance Testing in Multiple Sclerosis—Improving Neurological Assessment With Static Posturography? - Inojosa, Hernan; Schriefer, Dirk; Klöditz, Antonia; Trentzsch, Katrin; Ziemssen, Tjalf (Frontiers in Neurology, 2020)
Background. Balance problems can severely limit quality of life of people with Multiple Sclerosis (pwMS) already in early stages of the disease. PwMS are usually assessed with the Expanded Disability Status Scale (EDSS), which includes a Romberg Test for assessing balance. As the EDSS assessments are subjective to the examining neurologist, the postural stability of pwMS could be objectively quantified by the implementation of static posturography to detect balance problems and address preventive medical care. Methods. In this cross-sectional study, we added static posturography to the neurological EDSS examination in pwMS and healthy subjects to determine how this technique could supplement information to the evaluation of the cerebellar functional system of the neurostatus EDSS as clinical outcome already in early disease stages. Static posturography was performed with subjects standing on a force platform. As outcome variable, delineated area, average speed and average sway were obtained. Unpaired t-test as well as (Welch’s) Analysis of variance (ANOVA) with pairwise post-hoc comparisons according to Games-Howell were used. Spearman rank correlations were implemented to study associations of balance outcomes with EDSS-associated outcomes. Results. 99 pwMS (mean age: 35.01 years; EDSS median: 2.0, 68.69% females) and 30 healthy subjects (mean age: 34.03 years; 70% females) were enrolled. pwMS had worse performance of the three evaluated balance parameters than the healthy group (all p<0.001). Even patients without postural instability as documented in the Romberg test score of the EDSS assessment showed significantly worse outcome regarding the delineated area (+1.97 cm2, 95%-CI (0.61-3.34); p=0.002) versus healthy controls. Similar results were observed for the comparison between pwMS with normal cerebellar function EDSS-system and healthy subjects. There were significant correlations with the EDSS, cerebellar function score and Romberg test for the delineated area and average speed (r’s ranging from 0.330 to 0.537, p<0.001). Conclusions. Static posturography can complement neurological assessment of EDSS as objective and quantitative test especially for MS patients in early stages of the disease.